ANALISIS KEKUATAN STRUKTUR JEMBATAN TABAYANG DI KOTA TANJUNGBALAI MENGGUNAKAN METODE MOMEN INERSIA - Junaidi Siahaan; Adhyaksa Dealova Lubis; Rahmat Hidayat Samosir; Abdul Wahid Syabana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Structural analysis research on the Tabayang Bridge in TANJUNG BALAI City, North Sumatra. To determine the structural resistance of the Tabayang Bridge using the moment of inertia method formula,  The research on the resistance of the Tabayang Bridge, which has a total length of 600 m, the beam is divided into three cross-sectional segments (top, middle, web, and bottom with the following provisions): Upper flange (Concrete Plate): Width ????1 = 120 cm, Thickness ℎ1 = 20 cm. Web (Beam Web): Thickness ????2 = 15 cm, Height ℎ2 = 140 cm. Lower flange (Bottom Load): Width ????3 = 50 cm, Height ℎ3 = 30 cm. The results of the study indicate that the maximum bending stress that occurs (11.40 MPa) is smaller than the allowable compressive strength of the concrete (σ_permit = 15 MPa), so the Tabayang Bridge girder cross-section is declared SAFE against the planned bending load. The moment of inertia is a crucial parameter in bridge structural strength analysis because it determines the cross-section's ability to withstand bending forces and control deflection. The greater the moment of inertia, the greater the structural stiffness and the smaller the stress and deflection caused by loading. Therefore, calculating the moment of inertia is a key step in the planning and safety evaluation of bridge structures, ensuring that the resulting structure meets the strength, stiffness, and safety requirements of civil engineering standards. Keywords: Analysis of the durability of the Tabayang Bridge using the moment of inertia method  Abstrak: Penelitian analisa struktur Jembatan Tabayang di Kota TANJUNG BALAI Sumatra Utara ,Untuk mengetahui ketahanan struktur pada jembatan tabayang yang menggunakan rumus metode momen inersia, Penelitian ketahanan jembatan tabayang yang memiliki panjang total 600 m balok tersebut dibagi menjadi 3 segmen penampang (atas,tengah,web dan bawah dengan ketentuan), Flens atas (Plat Beton) : Lebar ????1 = 120 cm, Tebal ℎ1 = 20 cm. Web (Badan Balok) : Tebal ????2 = 15 cm, Tinggi ℎ2 = 140 cm Flens bawah (Beban Bawah) : Lebar ????3 = 50 cm, Tinggi ℎ3 = 30 cm. Hasil dari penelitian tersebut pada tegangan lentur maksimum yang terjadi (11.40 MPa) lebih kecil dari kuat tekan izin beton (σ_izin = 15Mpa), maka penampang gelagar Jembatan Tabayang dinyatakan AMAN terhadap beban lentur yang direncanakan. Momen inersia merupakan parameter penting dalam analisis kekuatan struktur jembatan karena menentukan kemampuan penampang dalam menahan gaya lentur dan mengendalikan lendutan. Semakin besar nilai momen inersia, semakin tinggi kekakuan struktur dan semakin kecil tegangan serta lendutan yang terjadi akibat pembebanan. Oleh karena itu, perhitungan momen inersia menjadi salah satu tahapan utama dalam perencanaan dan evaluasi keamanan struktur jembatan, sehingga konstruksi yang dihasilkan memenuhi persyaratan kekuatan, kekakuan, dan keselamatan sesuai standar teknik sipil. Kata Kunci: Analisis ketahanan Jembatan Tabayang Metode momen inersia.